PERAN SERTIFIKASI HAK MILIK TANAH DALAM MENDUKUNG INKLUSI KEUANGAN DAN PENINGKATAN KESEJAHTERAAN SOSIAL MELALUI AKSES PERMODALAN PADA LEMBAGA KEUANGAN FORMAL - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. ADIBA AISHA AMIRA, 2025)
This study examines the role of land title certification in supporting financial inclusion and improving social welfare through access to capital in formal financial institutions. Using a literature review approach, this study examines literature and empirical studies that link legal certainty of land ownership with ease of access to capital for the community, especially vulnerable groups. The results of the study show that land certification provides legal certainty that encourages financial institutions to distribute credit more widely and safely, thereby expanding access to formal finance. This access to capital plays an important role in strengthening the economic capacity of the community, increasing business productivity, and promoting sustainable social welfare. However, to optimise the role of land certification, policy synergy, inclusive financial product innovation, and public education are needed to ensure that capital utilisation is effective and has a broad impact.